Early enteral nutrition in surgical treatment of an acute complicated pancreatitis - V. P. Andriushchenko; D. V. Andriushchenko; V. V. Kunovskyi; Yu. S. Lysiuk (Клінічна хірургія)
Objective. To estimate the efficacy of early enteral nutrition (EEN) in patients with an acute complicated pancreatitis, after determining of its content  and improving the realization methods.